(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
Tourism in is one of the most efficient and competitive industries in Croatia. According to the Croatian National Bank (2015), with an income of 7.4 billion Euros in 2014, it contributes 17.2% to the national GDP. From the marketing point of view, it is one of the most crucial images of Croatia internationally. However, for decades tourism in Croatia was marked as “3S” (sun, sand and sea). This means that its competitiveness was based primarily on natural resources. Apart from price differentiation, such positioning has removed the characteristics that differentiate it from other Mediterranean destinations and has resulted in the existing problems of high seasonality, low ROI, low value added, etc. The major goal of this paper is to analyse the opportunity of increasing the tourism value added by developing food tourism as a special tourist product of Croatia. The research is in line with the goals of the national tourism development strategy which emphasizes the need to create value added to the national economy by valorisation and protection of available resources, market repositioning and new identity creation as well as enabling additional market opportunities for local products. Food tourism perfectly matches these goals. A pilot research of supply (hotels and restaurants, local tourist associations, souvenir shops) and demand (foreign tourists) was conducted and potential for such development was identified. The gaps in attitudes and opinions between supply and demand of food tourism is analysed and discussed and appropriate marketing activities are suggested. Keywords: Food tourism, Croatia, marketing, competitiveness